2021
DOI: 10.1155/2021/3461648
|View full text |Cite|
|
Sign up to set email alerts
|

Healthcare Data-Based Prediction Algorithm for Potential Knee Joint Injury of Football Players

Abstract: It is important to predict the potential harm to the knee joint in order to prevent football players from inflicting numerous injuries to the knee during activity. Numerous professionals have been drawn to this subject, and many viable prediction systems have been developed. Prediction of potential knee joint injury is critical to effectively avoid knee joint injury during exercise. The current prediction algorithms are mainly implemented through expert interviews, medical reports, and historical documents. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Furthermore, the effect of irregular particle shapes is a highly nonlinear phenomenon that the standard least-squares fitting method cannot adequately capture . Recently, the artificial neural network (ANN) approach has been proposed as an effective tool for the analysis of complex systems, across several fields, including science, engineering, healthcare, and finance. Coupled with other data analysis tools, ANN has the potential to improve the analysis of complex systems significantly …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the effect of irregular particle shapes is a highly nonlinear phenomenon that the standard least-squares fitting method cannot adequately capture . Recently, the artificial neural network (ANN) approach has been proposed as an effective tool for the analysis of complex systems, across several fields, including science, engineering, healthcare, and finance. Coupled with other data analysis tools, ANN has the potential to improve the analysis of complex systems significantly …”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%